Vitamin D content in food supplements - Djermanović, Mirjana; Bojanić, Ljubica (Archives of Pharmacy, 2022)
Vitamin D is a liposoluble vitamin that has numerous and significant roles in the human body. Daily needs for vitamin D are met throuh food intake and sun exposure, which enables the synthesis of this vitamin in the skin. Vitamin D affects the process of mineralization of the skeletal system. Vitamin D deficiency is a major cause of rachitis. Vitamin D plays an important role in the function of the immune system and it affects both innate and aquired immunity. Our goal was to determine the quality of dietary supplements when it comes to vitamin D content. We mapped products that are already on the market of the Republic of Srpska and contain vitamin D. Aso, we investigated the compliance of the declared content of vitamin D on the package with actually determinated content. Our research showed that most of the samples complied health safety requirements. One sample in tablet pharmaceutical form did not have the appropriate content of vitamin D (it was lower than the declared one). The quality of food supplements and their active ingredients affect the overall health, because the composition and its purpose are the main reason of placing such products on the market. Therefore, it is necessary to control the qualitative and quantitative composition, especially the active ingredients, in addition to the usual health parameters for a particular category. In general, the quality of food supplements should be an imperative for both, producers and food business operators who place them on market.